1961
DOI: 10.1083/jcb.11.3.651
|View full text |Cite
|
Sign up to set email alerts
|

Motion Picture and Electron Microscope Studies on the Embryonic Avian Osteoclast

Abstract: Timeqapse motion picture studies were carried out on isolated fowl embryo osteoclasts in vitro; the cells have an extremely active ruffled border, and show vigorous pinocytotic activity. Electron microscope studies on osmium-fixed cells showed that the pinocytotic vacuoles contained bone salt crystals (as well as material which could not be identified on morphological grounds), and that the folds of the ruffled border enclosed crystals and collagen fibrils. Changes were seen in the matrix beneath the ruffled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1964
1964
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…About 35 to 40%o of total body collagen is found in bone matrix (26), which in turn constitutes about 30% of the dry weight of bone (27). Osteoclasts may play a role in the process whereby Ca V. parathyroids induce breakdown of bone (28,29); the increase in OHPr excretion presumably results from this breakdown of bone and of insoluble bone collagen. It is not clear, however, whether the collagen of organic matrix is altered directly, or after the salts have been removed.…”
Section: Resultsmentioning
confidence: 99%
“…About 35 to 40%o of total body collagen is found in bone matrix (26), which in turn constitutes about 30% of the dry weight of bone (27). Osteoclasts may play a role in the process whereby Ca V. parathyroids induce breakdown of bone (28,29); the increase in OHPr excretion presumably results from this breakdown of bone and of insoluble bone collagen. It is not clear, however, whether the collagen of organic matrix is altered directly, or after the salts have been removed.…”
Section: Resultsmentioning
confidence: 99%
“…Odontoclasts seem to play an important role in root resorption. However, studies of odontoclasts (Yaeger and Kraucunas, 1969;Freilich, 1971) are still few in comparison with those on osteoclasts in bone resorption (Hancox and Boothroyd, 1961;Lucht, 1972;Bonucci, 1974;Heersche, 1978;Boyde et al, 1984;Tanaka and Tanaka, 1988). Existing studies have been restricted to the physiological root resorption in deciduous teeth induced by the eruption of permanent teeth (Furseth, 1968).…”
Section: Introductionmentioning
confidence: 97%
“…4 The brush or ruffled border of the osteoclast actively sweeps across the bone or dentin to produce the enzymatic destruction of the connective tissue matrix and the dissolution of the minerals contained in this matrix. 5 It has been found that gallium is absorbed preferentially in bone and that, as a consequence, gallium increases the stabilizing of hydroxyapatite crystals. 6,7 Other investigators suggested that gallium can be absorbed into the inorganic crystalline substructure of bone or dentin, which alters the material enough to resist specifically dissolution by the osteoclast.…”
Section: Introductionmentioning
confidence: 99%